Scale Dependent Loss of Global Form Perception in Strabismic Amblyopia - Rislove, Elizabeth M. (2010)
Amblyopic humans are known to have a range of spatial vision abnormalities. Prior studies have documented amblyopic deficits in global form perception, but have typically used only one set of stimulus parameters. Our aim in this study was to examine the extent and nature of global form perception deficits in strabismic amblyopia using a range of spatial scales and pattern types. Glass patterns are random dot stimuli in which the local orientations of paired dots must be integrated over space to yield a global form percept. We measured coherence thresholds for discrimination of pattern structure in translational (linear) and concentric Glass patterns at three spatial scales in two control and six amblyopic observers. We found that sensitivity to Glass patterns depended on both spatial scale and pattern type in all observers. Participants with a history of abnormal early visual experience showed greater interocular threshold difference when the discrimination was based on translational patterns than when it was based on concentric patterns, and the degree of amblyopic loss was greatest at fine spatial scale. Our results show that the nature and extent of global form vision deficits vary substantially with stimulus parameters, and are greatest at fine spatial scales.